A CHIP fellow's transition into practice: Building a complex coronary therapeutics program. Issue 5 (25th November 2019) - Riley, Robert F.; Henry, Timothy D.; Kong, James A.; Reginelli, Joel P.; Kereiakes, Dean J.; Grantham, J. Aaron; Lombardi, William L.
Abstract: Background: Both the prevalence and complexity of coronary artery disease are on the rise in the United States, leading to a resurgence in novel techniques and equipment utilized to treat complex coronary disease. However, declining percutaneous coronary intervention (PCI) volumes and lack of formal post‐graduate education opportunities have created a gap in treatment delivery for this patient population. Several complex, high‐risk, and indicated PCI (CHIP) fellowships have been developed in an attempt to bridge this disparity. We present data from the first year of practice from a former CHIP fellow during development of a formal complex coronary therapeutics program. Methods: Data was prospectively collected for PCIs performed during the first 12 months of practice for the lead author and compared to procedures performed in the 12 months prior to the study period. Results: Out of 371 PCIs performed during the study period, 53.4% (198/371) were considered complex, including 126 chronic total occlusion (CTO) procedures. Compared to the previous 12 months, there was a significant increase in the number and complexity (median J‐CTO score 2.1 vs. 1.3, p .04) of CTOs performed during the study period. CTO procedural characteristics and complication rates were similar to those previously published in large U.S. registries, with technical success in 93.4% (118/126) and procedural success in 85.7% (108/126). Conclusion: Following dedicated CHIP fellowship training and establishment of a formal CHIP program, procedural success and complication rates were achieved similar to those published in prior studies evaluating CTO PCI at high volume centers.